2017
DOI: 10.1523/jneurosci.3761-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Modulation of Intrinsic Excitability in Rat Prelimbic Cortex Neuronal Ensembles and Non-Ensembles after Operant Learning

Abstract: Learned associations between environmental stimuli and rewards drive goal-directed learning and motivated behavior. These memories are thought to be encoded by alterations within specific patterns of sparsely distributed neurons called neuronal ensembles that are activated selectively by reward-predictive stimuli. Here, we use the Fos promoter to identify strongly activated neuronal ensembles in rat prelimbic cortex (PLC) and assess altered intrinsic excitability after 10 d of operant food self-administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
6
38
0
Order By: Relevance
“…Taken together, this indicates that training to self-administer drug (cocaine) and nondrug (sucrose) reinforcers produce qualitatively similar reductions in intrinsic inhibition early on, but for drug reinforcers these modifications are persistent even after withdrawal or extinction. These data are consistent with previous studies reporting that drug and nondrug reinforcers produce different cellular adaptations in PL-PFC neurons (Whitaker et al, 2017).…”
Section: Loss Of Inhibition Is Independent Of Extinction Training Andsupporting
confidence: 93%
See 2 more Smart Citations
“…Taken together, this indicates that training to self-administer drug (cocaine) and nondrug (sucrose) reinforcers produce qualitatively similar reductions in intrinsic inhibition early on, but for drug reinforcers these modifications are persistent even after withdrawal or extinction. These data are consistent with previous studies reporting that drug and nondrug reinforcers produce different cellular adaptations in PL-PFC neurons (Whitaker et al, 2017).…”
Section: Loss Of Inhibition Is Independent Of Extinction Training Andsupporting
confidence: 93%
“…Activity-induced increases in Fos are considered to represent the integration of neuronal activity driven by numerous synaptic alterations (Cifani et al, 2012;Koya et al, 2012;Whitaker et al, 2017;Ziminski et al, 2017a;2017b). Using cFos-GFP transgenic rats, we observed that cocaine-SA training decreased intrinsic inhibition selectively in cFos/GFP + neurons.…”
Section: Select Adaptations In a Subpopulation Of Pl-pfc Neuronsmentioning
confidence: 65%
See 1 more Smart Citation
“…Future studies will investigate the role that co-activation of these neurons during concurrent Meth and sex plays in enhanced drug-seeking behavior in extinction or reinstatement. It has been demonstrated in both drug-and food-seeking studies that neurons encoding extinction memories versus those encoding reward memories reside in the mPFC (ventral mPFC and dorsal mPFC, respectively) [52,53], and that expression of these memories is abolished when these neurons are selectively lesioned [54,55]. It is likely, therefore, that distinct neuronal ensembles are implicated in the failure to suppress behavior during the initial phases of extinction learning versus during the expression of drug-associated memory in reinstatement in the concurrent Meth/sex animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although muscimol and baclofen inactivation is widely used, this manipulation may produce a strong inhibitory effect that overwhelms the function of discrete subsets of neurons that could regulate distinct behavioural effects. Indeed, studies have shown that behaviour can be regulated by small ensembles of neurons in a brain area such as the medial prefrontal cortex (Whitaker et al, 2017), and that eliminating different ensembles within the same region can produce dissociable effects on behaviour (Pfarr et al, 2015). A more selective approach may therefore be necessary to parse with greater specificity the contribution of PL and IL subregions to motivated behaviour produced by appetitive Pavlovian conditioning.…”
Section: Csmentioning
confidence: 99%